Cloning and Characterization of TpNRAMP3, a Metal Transporter From Polish Wheat (Triticum polonicum L.) - Peng, Fan; Wang, Chao; Cheng, Yiran; Kang, Houyang; Fan, Xing; Sha, Lina; Zhang, Haiqin; Zeng, Jian; Zhou, Yonghong; Wang, Yi (Frontiers in Plant Science, 2018)
Essential transition metals and non-essential metals often co-exist in arable soils. In plants, some transition metal transporters, such as the natural resistance-associated macrophage proteins (NRAMPs), poorly selectively transport metals with similar chemical properties whether they are essential or non-essential. In this study, a member of the NRAMP transporter family, TpNRAMP3, was identified from dwarf Polish wheat (Triticum polonicum L.). TpNRAMP3 encodes a plasma membrane-localized protein and was highly expressed in leaf blades and roots at the jointing and booting stages, and in the first nodes at the grain filling stage. Expression of TpNRAMP3 increased sensitivity to Cd and Co, but not Zn, and increased the Cd and Co concentrations in yeast. TpNRAMP3 expression in Arabidopsis increased concentrations of Cd, Co and Mn, but not Fe or Zn, in roots, shoots and whole plant. However, TpNRAMP3 did not affect translocation of Cd, Co or Mn from roots to shoots. These results suggest that TpNRAMP3 is a transporter for Cd, Co and Mn accumulation, but does not transport Fe or Zn. Because Cd and Co are nonessential toxic metals, selective genetic manipulation of TpNRAMP3 will help breed low Cd- and Co-accumulating cultivars.